Family influence on the consumption of sugary drinks by children under two years old - Jaime, Patricia Constante; Prado, Rogério Ruscitto do; Malta, Deborah Carvalho (Revista de Saúde Pública, 2017)
OBJECTIVE To evaluate the influence of family habits and household characteristics on the consumption of sugary drinks by Brazilian children under two years old. METHODS This was a cross-sectional study that used secondary data generated by the National Health Survey (PNS) in 2013. We studied 4,839 pairs of children under two years old and adults living in the same house. We estimated the prevalence of the indicator of sugary drinks consumption for the total sample of children and according to family and household variables. We applied multiple logistic regression analysis to evaluate the influence of family habits and household characteristics on the consumption of sugary drinks by the children. RESULTS The consumption of sugary drinks was identified in 32% of the studied children (95%CI 30.6-33.3) and was independently associated with the following family and household characteristics: regular consumption of sugary drinks by the adult living in the house (OR = 1.78; 95%CI 1.51-2.10), watching TV for more than three hours per day (OR = 1.22; 95%CI 1.03-1.45), older age (OR = 3.10; 95%CI 1.54-6.26), greater education level (OR = 0.70; 95%CI 0.53-0.91), house located in the Northeast region (OR = 0.65; 95%CI 1.54-6.26), and number of family members (OR = 1.05; 95%CI 1.00-1.09). CONCLUSIONS Our findings indicate the high prevalence of sugary drinks consumption by Brazilian children under two years old and show that sociodemographic characteristics and family habits affect this feeding practice not recommended in childhood.